FOSTERING EMPLOYEE COMMITMENT IN PHARMACEUTICAL COMPANY THROUGH GREEN HUMAN RESOURCES MANAGEMENT - Anindita, Rina; Rapiah, Siti Nur (Universitas Brawijaya, Indonesia, 2023)
Currently, companies are faced with competition not only to get the best talent but to retain competent employees in the company, especially in the Pharmaceutical Industry, which in a pandemic situation still survives in the market. Companies need to create a strategy that can support increased employee commitment, and Employer Branding can be one of the strategies that can build a positive view so that it can influence employees to stay in the company. This research aims to analyze the effect of Employer Branding, Green Human Resources Management (GHRM), on Corporate Reputation and Employee Commitment among employees who understand GHRM with at least 1 year working period as a permanent employee in the Pharmaceutical Industry. This research was conducted on 238 respondents who met the research criteria, by distributing online questionnaires. The data processing method uses Structural Equation Modeling (SEM)-Partial Least Square (PLS). The research found that Employer branding has an influence on company reputation, but employer branding has no effect on employee commitment. Then, Green Human Resources Management (GHRM) has an influence on company reputation, company reputation has an influence on employee commitment, and green human resources management (GHRM) has a role that can affect employee commitment. This condition requires an active role of leaders in dealing with talent war condition in talent market by finding effective ways to retain competent employees in the company by fostering a sense of commitment in employees. Leaders in the company need to create better plans which support increased employee commitment, one of the plans is optimizing employee involvement through the application of green human resources management (GHRM). In this condition, leaders must play an active role to increase employee's commitment, such as clarifying the goals that the company wants to achieve, involving employees in every decision or policy making in the team, and increasing employees' emotional feelings towards the company by paying attention to employee comfort at work and in the work environment.